Identification of Three Novel Plasmodium Factors Involved in Ookinete to Oocyst Developmental Transition - Ukegbu, Chiamaka V.; Christophides, George K.; Vlachou, Dina (Frontiers in Cellular and Infection Microbiology, 2021)
Plasmodium falciparum malaria remains a major cause of global morbidity and mortality, mainly in sub-Saharan Africa. The numbers of new malaria cases and deaths have been stable in the last years despite intense efforts for disease elimination, highlighting the need for new approaches to stop disease transmission. Further understanding of the parasite transmission biology could provide a framework for the development of such approaches. We phenotypically and functionally characterized three novel genes, PIMMS01, PIMMS57 and PIMMS22, using targeted disruption of their orthologs in the rodent parasite Plasmodium berghei. PIMMS01 and PIMMS57 are specifically and highly expressed in ookinetes, whilst PIMMS22 transcription starts already in gametocytes and peaks in sporozoites. All three genes show strong phenotypes associated with the ookinete to oocyst transition, as their disruption leads to very low numbers of oocysts and complete abolishment of transmission. PIMMS22 has a secondary essential function in the oocyst. Our results enrich our molecular understanding of the parasite-vector interactions and identify PIMMS01, PIMMS57 and PIMMS22 as new targets of transmission blocking interventions.